When war is justified : a study in the causes of early Islamic wars - Gilani, Sayyid Muhammad Yunus; Islam , Tajul (Serials Publications, 2011)
Infliction of a war is often followed by an ethical question whether it is just or unjust. A war can only be justified if it has enough just causes. This study aims to investigate the Islamic justifications of war through analyzing firstly the Qur’anic directives of war; secondly, the background of the wars that were fought by Muhammad (s.a.w.) as well as his companions. Finally, a brief comparison between the wars in the Prophetic ear and the First World War is made so that the ideal of justification of Islamic wars is visualized.